Pembinaan Mutu Pondok Pesantren Nurul Huda di Kepulauan Gili Raja Desa Banbaru Kecamatan Gili Genting Kabupaten Sumenep Jawa Timur - Abd Syakur; Fairuzah Fairuzah; Syafiqurrahman Syafiqurrahman; Paisun Paisun (LPPM Universitas Yudharta Pasuruan, 2020)
The purpose of this activity is to provide guidance and assistance in improving the quality of the Nurul Huda Islamic Boarding School, Banbaru Village, Gili Genting Sumenep District. Guidance is needed to improve the quality of education Islamic Boarding School, considering that Islamic Boarding School are required to be educational institutions capable of producing quality students, both from an intellectual, religious and moral perspective, as well as being able to manage the potential that exists in the Gili Raja islands. Meanwhile, the Nurul Huda Islamic Boarding School in the Gili Raja Islands, Banbaru Village, Gili Genting, is considered to have not been maximal in producing quality students. This is because management is managed very simply and traditionally, there is a lack of human resources for education and education personnel, a curriculum that is not well organized, and there is no skills education for students. Therefore, to improve the quality of the Nurul Huda Islamic Boarding School, it is necessary to provide assistance and guidance by providing seminars on the urgency of education Islamic Boarding School in the contemporary era, training in curriculum preparation and training in management Islamic Boarding School, strengthening human resources (HR) for educators and education personnel, and providing entrepreneurial training. The hope of this mentoring and coaching service is that Nurul Huda Islamic Boarding School has insight into Islamic Boarding School reform, has a curriculum that is oriented towards meeting the demands and needs of the community, has good management, increases human resources for educators and education personnel, and implants an entrepreneurial spirit for teachers and students or protege.